2018
DOI: 10.1097/pcc.0000000000001615
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Massage and Reading on Children’s Pain and Anxiety After Cardiovascular Surgery: A Pilot Study*

Abstract: Our pilot study demonstrated the safety and feasibility of implementing massage therapy in the immediate postoperative period in pediatric heart surgery patients. We found decreased State-Trait Anxiety scores at discharge and lower total exposure to benzodiazepines. Preventing postoperative complications such as delirium through nonpharmacologic interventions warrants further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…Although the parents were requested to apply moderate pressure, there were no compliance checks on the parents’ massages in this study. In a study on pain and anxiety after cardiovascular surgery, sixty children were randomly assigned to receive three massage sessions or three reading visits on the first three postoperative days [48]. The children receiving massage therapy had significantly lower anxiety scores and lower total benzodiazepine exposure for the three days following heart surgery.…”
Section: Child and Adolescent Massage Therapymentioning
confidence: 99%
“…Although the parents were requested to apply moderate pressure, there were no compliance checks on the parents’ massages in this study. In a study on pain and anxiety after cardiovascular surgery, sixty children were randomly assigned to receive three massage sessions or three reading visits on the first three postoperative days [48]. The children receiving massage therapy had significantly lower anxiety scores and lower total benzodiazepine exposure for the three days following heart surgery.…”
Section: Child and Adolescent Massage Therapymentioning
confidence: 99%
“…Nonetheless, preventing or effectively treating withdrawal syndrome might reduce the number of subsequent readmissions. Proposed measures for doing so include better selection of analgesics, implementation of nurse‐driven analgesic and sedation protocols, and administration of opioid‐weaning treatments and massage therapy . Although further studies are needed, multidisciplinary team approaches may reduce the incidence of withdrawal syndrome and, consequently, readmission.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, van Dijk et al exhibited that massage therapy has no considerable influence on the reduction of respiratory changes in children who suffered from burns (28). Similarly, Staveski et al reported that massage does no significantly mitigate post-surgical pain in children (29).…”
Section: Discussionmentioning
confidence: 99%